Current status of parasitic infections among Pangkor Island community in Peninsular Malaysia - A. F., Ahmad; Romano, Ngui; Muhammad Aidil, Roslan; Yvonne Ai Lian, Lim; Rohela, Mahmud (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2014)
Limited data is available on the prevalence of parasitic infections among the island communities in Malaysia with most studies performed between 1960s-1980s. This study was conducted to determine the current prevalence status of parasitic infections among communities living in Pangkor Island Peninsular Malaysia. A total of 131 stool and 298 serum samples were collected and subjected to microscopic examination for intestinal protozoa and helminths and detection of Toxoplasma gondii antibodies using commercial ELISA kits respectively. In addition, thin and thick peripheral blood films were microscopically screened for the presence of Plasmodium spp. and microfilariae respectively. The overall prevalence of intestinal parasitic infections among Pangkor Island community was 9.9% (13/131) with T. trichiura (5.3%) being the most common intestinal parasite detected. Toxoplasmosis was reported in almost 60% of the community with the seroprevalence being significantly high among females (64.7%) compared to males (52.8%) (p=0.038). None of those examined samples were infected with intestinal sarcocystosis, malaria and filariasis. This study revealed that the prevalence of intestinal parasitic infections among Pangkor Island community has been greatly reduced compared to that reported 35 years ago. Massive improvements in the socioeconomic status, personal hygiene, water facilities and sanitation may have contributed to the low prevalence of parasitic infections in this community. Nevertheless, further studies still need to be performed to determine the possible risk factors for the high prevalence of toxoplasmosis in this community.